Explaining recently arrived refugees' labor market participation: The role of policy characteristics among Syrians in the Netherlands - Damen, Roxy Elisabeth Christina; Huijnk, Willem; Dagevos, Jaco (Frontiers in Human Dynamics, 2023)
Various studies have indicated the disadvantaged positions of refugees on the labor market and studied various characteristics explaining this. Yet, little is known about the impact of settlement policy characteristics on recent arrivals’ labor market participation, despite them being heavily subject to such policies. We argue such policies, next to individual characteristics, can serve as a means to gather resources relevant to the host country and consequently labor market positions, but can also serve as a post-migration stressor obstructing this. Using the Netherlands as an example, we contribute to studies on the refugee gap and provide insight into key policy characteristics explaining recently arrived refugees’ (finding) employment. We use two-wave panel data of 2379 recently arrived Syrian refugees in the Netherlands, including data on key policy and individual characteristics combined with administrative data. Employing a hybrid model, we show both within- and between-person variation. Results indicate policy matters: short and active stays in reception, complying with the civic integration obligation and a lower unemployment rate in the region refugees are randomly assigned to are beneficial for Syrians’ (finding) employment. Like for other migrants, various forms of individual human capital also play a role.